(untitled) (Perner’s Contacts, 2010)
This paper deals with a problematic of transportation technology for packets and small individual packages. They stressed the specifics regarding the technical procedures applied in the event of deviations from normal procedures, with which may be often encountered. Attention is given to the less frequent practice during transportation of consignments.